Bioassay-guided fractionation of Euphrasia pectinata Ten. and isolation of iridoids with antiproliferative activity. (June 2015) - Marcotullio, Maria Carla; Loizzo, Monica Rosa; Messina, Federica; Temperini, Andrea; Tundis, Rosa; Menichini, Francesco; Curini, Massimo
Graphical abstract: Bioguided analysis of non-polar metabolites from Euphrasia pectinata led to the isolation of four iridoids that were tested for their cytotoxic activity against different tumor cell lines. Highlights: From the methanol extract of E. pectinata, the new iridoid Euphrasin was isolated. Its structure was determined by NMR spectroscopy. Euphrasin was active against LNCaP and HeLa cells. Abstract: The use of aerial parts of Euphrasia pectinata Ten. usually known as Eyebright, is one of the commonest folk remedy in many European and Asian countries to treat eye problems. By a bioassay-guided fractionation of the dichloromethane fraction of E. pectinata methanolic extract, following the antiproliferative activity on different cancer cell lines (MCF-7, HeLa, LNCaP, ACHN and C32), the new iridoid euphrasin (1 ), and the known campsinol (2 ), artselaenin A (3 ), and artselaenin B (4 ) were isolated. The structure of euphrasin (1 ) was determined by spectroscopic methods. All compounds screened by SRB assay exhibited antiproliferative activity in a concentration dependent-manner. In particular, euphrasin (1 ) showed a promising activity against LNCaP and HeLa cells with IC50 values of 0.1 and 0.2 μM, respectively. Signficative results were also obtained with campsinol (2 ) with IC50 value of 1.9 μM on endometrial cancer cells.